Comparison of Standard and Racing Roller Weight Variations on CVT on the Power and Torque of the Honda Beat 110cc - Efendi, Adhim Gustiar; kusbandono, Hermanu (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
This automatic motorbike uses an automatic transmission system called CVT (Contynously Variable Transmission). CVT is a system that automatically changes speed according to engine speed. This machine does not use transmission gears, but instead uses two pulleys (front and rear) which are connected by a belt (v-belt. The advantege of a CVt automatic transmission is that it can provide speed changes in torque from the engine to the rear whells automatically. This research aims to determine the effect of roller weight on the power and engine torque of a 110 cc two wheeled vehicle. The background of this research is to determine the power and torque of motorbikes for each roller weight studied and to draw conclusions about better use of rollers weight. This research uses experimental research methods, the materials used are standard 12gr,11gr,10gr,9gr,8gr rollers, as a comparison and 110cc injection beat motorbikes. The toll used in this research is a dynamometer. This tool shows directly the maximum power results at a certain rpm. Changes in the weight of the Honda Beat 110cc CVT roller affect the power produced by the engine. Changes in roller weight can affect the size of the engine’s power and torque. This in proven by data showing changes in engine power and torque during each test. Therefore, it is hoped that the result of this test can be used as a reference for improving engine peformance in vehicles.